Customer Retention & Customer Relationship Marketing: Strategi Pemasaran yang Potensial - Ariesya Aprilia (Jurnal Manajemen Maranatha, 2004)
The traditional marketing approach advocates the marketing mix principles and the quest for market share dominance through mass marketing techniques and a focus on new customer acquisition. This approach has guided managers for decades in planning in implementing their marketing strategies. But nowadays, traditional approach has been changed by customer retention. Customer retention, in the traditional marketing approach, is however seen as the 'end' rather than the means to delivering long-term profitability to firms. Customer retention should be part of the strategic marketing plan process and potentially potent marketing management strategy. Relationship marketing is concerned with how organizations manage and improve their relationships with customer for long-term profitability. Customer relationship marketing (CRM), which is becoming a topic of increasing importance in marketing, is concerned with using technology information (IT) in implementing relationship marketing strategies. It is integrated approach to managing relationships by focusing on customer retention and relationship development. Retaining good customers (or that may become good) is one of the most importance topics in customer retention and customer relationship marketing. This paper discusses key issues pertaining to customer retention management and customer relationship.